الوقف وأثره في تحقيق الأمن الاجتماعي - داود، هايل عبدالحفيظ; سيلغروفا، برلنت (جامعة آل البيت, 2019)
الوقف من أهم الطاعات التي يتقرب بها العبد إلى الله تعالي، لما فيه من منفعة للموقوف عليهم، وتفريج كرباتهم، ودفع حاجاتهم بصورة مؤسسية دائمة، لا بشكل آني مؤقت، والوقف له دور كبير في حفظ الأمن الاجتماعي وسد حاجة قطاع عريض من الفئات الاجتماعية، مما يحول دون انحرافها أو خروجها على القانون أو إحداث الشروخ الاجتماعية في المجتمع، وله دور مهم في التكافل الاجتماعي بل وفي التنمية الاقتصادية. إن مؤسسة الوقف اليوم لم يعد لها نفس الأثر والدور الذي كانت تمارسه في السابق، ولابد من البحث في سبل تفعيلها وإحياء دورها، ولذلك قام الباحثان في هذا البحث بالتعريف بالوقف ومشروعيته، ثم بيان الدور الكبير للوقف في تحقيق الأمن الاجتماعي بكل مجالاته من حيث: الرعاية الاجتماعية والصحية، والنهضة العلمية والاقتصادية، والدفاع عن الأمة، والدعوة إلى الله، وحفظ الأمن الداخلي للمجتمع، كما قدما في المبحث الثالث بعض الاقتراحات التي يمكن أن تسهم في تفعيل الوقف اليوم وإعادته إلى سابق عهده.
The charitable Islamic endowment is one of the most important good deeds in which Muslim draws closer to Allah. The donated assets based on charitable Islamic endowment method 'Waqf' can help those who are in need and relieve their miseries continuously and institutionally. Waqf can play a crucial role in achieving our social security and filling the need of a wide range of social groups as well as accomplishing social solidarity and developing our economy. Waqf also can save those who are in need from breaking the law in their endeavors to meet their life requirement or creating social strife in our societies. The Waqf Foundation today no longer has the same effect and role that can play in the past. Thus, it has become necessary to find out new methods to put Waqf into action once again in our modern life. This study aims to define the Waqf as Islamic terms and proving its legitimacy based on Islamic original sources. The researchers have also discussed the prominent role of the Waqf in achieving social security in all aspects of our social and health welfare as well as scientific and economic renaissance. The researcher also has come to some suggestions that could contribute to activating Waqf today and restore its role as it was in past.
Keywords: الوقف الخيرى -- التكافل الاجتماعى -- الأمن الاجتماعى